Russian Business: on the Way to Legalization? - Вадим Валерьевич Радаев (Journal of Economic Sociology, 2010)
Rather big business representatives still use grey schemes for their operation but they are discussing seriously the necessity for the legalization. The costs of the legalization are too high; moreover there are other obstacles on the way to implement it. Is the legalization really possible? How should the relations between business and authorities be built? These are the questions of the study, conducted in 2001. The data base was constructed from the focused interviews with the heads of import companies of electrical and computer appliances, participating in the business association of RATEK. The main focus was the comparative evaluation of the costs of different schemes of operations with customs.